Deploying Steerable Sheath to Improve Safety, Efficiency, and Efficacy of Body and Peripheral Interventions - Techasith, Tust; Mesipam, Avinash; Misono, Alexander S. (Journal of Clinical Interventional Radiology ISVIR, 2025)
Steerable vascular sheaths are designed to be used in the human vasculature to facilitate the introduction of diagnostic and/or therapeutic devices. Despite a broad indication, steerable sheaths are most commonly used in aortic intervention, particularly when there is a need for access through fenestrations. However, steerable sheaths have a wide variety of interventional radiology (IR) applications in the body and periphery. In this case series, we review the use of a steerable sheath in diverse applications, including arterial embolization, arterial thrombectomy/thrombolysis, stenting/recanalization, urinary, and foreign body retrieval. Steerable sheaths are found to provide enhanced stability of access, improved pushability, maintenance of access, control of directionality (i.e., steerability), and/or a combination of these factors. Steerable sheaths have broad uses in the body and peripheral far beyond their typical use in endovascular aortic work. Adoption of these techniques allows for improved safety, efficacy, and efficiency of several IR procedures.
Keywords: endovascular; procedures; embolization; therapeutic; thrombectomy; stents; foreign bodies